Symposium Review: The Impact of Fatty Acids as Bioactive Nutrients on the Development of Offspring - Carranza Martin, Ana Cristina (2024)
Fatty acids (FA) are normally considered a source of energy; however, some FA are essential nutrients with different biological functions such as ligands to membrane and nuclear receptors, and upon binding they modify cell function and transcript expression. The bioactive effects of the FA depend on the FA type and family (i.e., n-6 vs n-3). The FA effects on developmental programming have been studied in cattle and sheep with some similarities in the outcomes between species. Feeding n-3 FA during late gestation improves offspring production performance (i.e., milk yield in dairy cows and growth in beef cattle and sheep) compared with the offspring of dams supplemented with mono- and unsaturated FA or with offspring of dams with no FA supplementation. Also, there is a sexual dimorphism in the outcomes of n-3 FA supplementation, where the increase in growth due to n-3 FA seems to be more evident in males; but it might decrease growth in females. There are multiple assumptions as to how this physiological process occurs. Based on published literature, the developmental effect does not appear to be due to changes in hypothalamic regulations of dry matter intake and energy expenditure or liver and adipose tissue functions. The changes in offspring growth can be attributed to changes in gastrointestinal tract physiology, changes in immune response, or both, probably due to epigenetic changes in those tissues. Feeding n-3 FA in late gestation to the pregnant dam increases expression of amino acid transporters (mRNA and protein) in the offspring´s duodenum, associated with changes in DNA methylation. Regarding immune function, the increase in offspring performance has been associated with decreased haptoglobin after weaning in calves or increases in lipid mediators, such as resolvin-D1 at birth. Omega-3 supplementation during late gestation affects offspring growth; changes in the offspring´s gut and immune system biology can explain the sexual dysmorphism observed in changed body weight; however, we are unaware which of these basic mechanisms is responsible for the observed changes in biology.